(untitled) - Kudra, Tadeusz (New York, 2002)
Presents the most recent breakthroughs in thermal dehydration, drying, and dewatering. Emphasizes emerging equipment, innovative techniques, and cost-effective strategies for a variety of industrial and agricultural applications.
Các kỹ thuật chế biến thực phẩm hiện đại
Keywords: Drying